Original articleFamilial cerebral cavernous malformation - Dziedzic, Tomasz; Kunert, Przemysław; Matyja, Ewa; Ziora-Jakutowicz, Karolina; Sidoti, Antonella; Marchel, Andrzej (Folia Neuropathologica, 2012)
Cavernous malformations (CMs) occur in approximately 0.5% of the general population and represent 5-10% of the central nervous system vascular malformations. The majority of CMs appear sporadically but genetically determined familial forms account for 10% to 15% of all cases. The aim of this study was to discuss the clinical, pathological and genetic aspects of familial cerebral cavernous malformations (CCMs). We report on five members of a family who underwent surgery due to CCMs. However, only two members were treated in our Department. The age of onset of symptoms in these cases (4 men and 1 women) ranged from 3 to 28 years. Three members of the family were asymptomatic but it turned out that they were obligatory gene carriers and in one of them the cavernous malformation was confirmed by neuroimaging study. The clinical symptoms of CCMs included seizure (three patients) and focal neurological deficit (two patients). Multiple CCMs were identified in two symptomatic patients (two lesions) and in one asymptomatic patient (three lesions). The lesions were located superficially (4), in the basal ganglia (1), in the brainstem (2) and in the cerebellar vermis (1). In two patients, the subsequent imaging studies showed a single de novo CCM formation. Only one patient with mutation of CCM2 gene was treated surgically. In patients with cavernous malformations the detailed clinical and family history of neurological events ought to be collected. This is particular important in patients with multiple changes or with de novo CCMs formation, identified in subsequent imaging studies. A well-documented family history can help to establish the final diagnosis and makes it possible to offer all members of the family proper neurological and genetic care.